Sistem PPDB Online Berbasis Web di MTs Negeri 3 Purworejo - Imam Tri Suryadin Imam; Anwar, Aang Anwarudin; Wahyu, Wahyu Ikhsanudin; Lazuardi Fatahilah Hamdi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Acceptance of new students is one of the processes that exist in educational institutions such as schools which are useful for screening prospective students who are selected according to the criteria determined by the school to become their students. In general, the process of admitting new students is carried out through the stages of registration, selection tests, and announcement of student acceptance. In this research, its application to MTs Negeri 3 Purworejo, which has been done manually or online so far, but only uses the PPDB link, which allows for a lot of data shortages. The formulation of the problem of this research is how to create an information system for new student admissions at MTs Negeri 3 Purworejo. The methods used are literature, observation, analysis, design, testing and implementation. This new student admissions information system was built using the PHP programming language and utilizes the MySQL database as a database server. The result of this research is a web-based new student admissions information system that has the ability to make it easy for parents of prospective new students to obtain all information about new student admissions and carry out the online registration process.